THE MOTIVES OF EDUCATIONAL ACTIVITY STUDENTS OF PEDAGOGICAL EDUCATION - Eliseeva, Natalia; Pospelova, Olga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The article analyzes the problems of the development of educational and professional motivation students of pedagogical education in the course of their professional training in higher education. The purpose of the study was to substantiate theoretically and verify experimentally of formation of educational and professional motivation, students ' opinions about the problems of organization of educational process gives the opportunity to evaluate and adjust it from the perspective of a student as a subject of educational process.  To achieve this goal, we used the following methods: to collect empirical survey data (student questionnaires).The results of the study feature educational and professional motivation of contemporary students. According to the results of the experiment, the need to create special educational conditions that underlie the development and implementation of the program aimed at increasing the level of professional motivation of students of pedagogical education  in higher education is revealed.